Preoperative Applications of Navigated Transcranial Magnetic Stimulation - Haddad, Alexander F.; Young, Jacob S.; Berger, Mitchel S.; Tarapore, Phiroz E. (Frontiers in Neurology, 2021)
Preoperative mapping of cortical structures prior to neurosurgical intervention can provide a roadmap of the brain with which neurosurgeons can navigate critical cortical structures. In patients undergoing surgery for brain tumors, preoperative mapping allows for improved operative planning, patient risk stratification, and personalized preoperative patient counseling. Navigated transcranial magnetic stimulation (nTMS) is one modality that allows for highly accurate, image-guided, non-invasive stimulation of the brain, thus allowing for differentiation between eloquent and non-eloquent cortical regions. Motor mapping is the best validated application of nTMS, yielding reliable maps that have accuracy similar to intraoperative cortical mapping. Language mapping is also commonly performed, although the nTMS language maps are not as highly concordant with direct intraoperative cortical stimulation maps as the nTMS motor maps. Additionally, nTMS has been used to localize cortical regions involved in other functions such as facial recognition, calculation, higher-order motor processing, and visuospatial orientation. In this review, we evaluate the growing literature on the applications of nTMS in the preoperative setting. First, we analyze the evidence in support of the most common clinical applications. Then we identify usages that show promise but require further validation. We also discuss developing nTMS techniques that are still in the experimental stage, such as the use of nTMS to enhance postoperative recovery. Finally, we highlight practical considerations when utilizing nTMS and, importantly, its safety profile in neurosurgical patients. In so doing, we aim to provide a comprehensive review of the role of nTMS in the neurosurgical management of a patient with a brain tumor.